2013
DOI: 10.1128/cvi.00552-12
|View full text |Cite
|
Sign up to set email alerts
|

An Adenovirus-Based Vaccine with a Double-Stranded RNA Adjuvant Protects Mice and Ferrets against H5N1 Avian Influenza in Oral Delivery Models

Abstract: An oral gene-based avian influenza vaccine would allow rapid development and simplified distribution, but efficacy has previously been difficult to achieve by the oral route. This study assessed protection against avian influenza virus challenge using a chimeric adenovirus vector expressing hemagglutinin and a double-stranded RNA adjuvant. Immunized ferrets and mice were protected upon lethal challenge. Further, ferrets immunized by the peroral route induced cross-clade neutralizing antibodies, and the antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…We have also tested delivery of vaccines and drugs to ex vivo pig skin with these silicon microneedles3334 using accepted models of transcutaneous drug delivery; this gives us an initial level of confidence that these silicon microneedle patches will deliver vaccine in vivo to humans. Furthermore, we63536 and others1137 have also previously demonstrated that immunogenicity findings in mice for adenovirus-based vaccines can translate to humans. However, in the absence of clinical testing, we cannot predict if adenovirus-based vaccine administration using solid microneedle patches would result in the same effect on immunogenicity and protection in humans as was determined in this study.…”
Section: Discussionmentioning
confidence: 82%
“…We have also tested delivery of vaccines and drugs to ex vivo pig skin with these silicon microneedles3334 using accepted models of transcutaneous drug delivery; this gives us an initial level of confidence that these silicon microneedle patches will deliver vaccine in vivo to humans. Furthermore, we63536 and others1137 have also previously demonstrated that immunogenicity findings in mice for adenovirus-based vaccines can translate to humans. However, in the absence of clinical testing, we cannot predict if adenovirus-based vaccine administration using solid microneedle patches would result in the same effect on immunogenicity and protection in humans as was determined in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Fecal IgA responses were still elevated 6 months after immunization. In addition, there was no evidence that preexisting immunity to the recombinant Ad5 (rAd5) vector affected the ability to elicit a norovirus-specific immune response (see Supplemental Methods), which has been demonstrated in additional indications and studies using the same oral vaccine platform (17,27).…”
Section: Discussionmentioning
confidence: 98%
“…The vector also encodes a molecular dsRNA hairpin adjuvant driven by a separate promoter. Details of the rAd vector platform have been described previously (27). GMP drug substance was produced in HyClone Single Use Bioreactors (GE Healthcare Life Sciences) at Lonza Biologicals.…”
Section: Methodsmentioning
confidence: 99%
“…Oral administration of a live adenovirus-vectored vaccine abrogates the relevance of pre-existing vector immunity, resulting in a robust immune response to the delivered antigen [42,43,70,71]. The US company Vaxart, which is currently evaluating an oral adenovirus-based influenza vaccine in a Phase I clinical trial (NCT02547792), has also developed an oral adenovirus-based EVD vaccine with plans to enter clinical trials.…”
Section: Eplication-incompetent Vectored Vaccinesmentioning
confidence: 99%